(untitled) (Research, Society and Development, 2021)
The objective was to identify the functionality profile of the Brazilian elderly living in the community accompanied by primary care health teams. This was an integrative review developed between March and July 2020, using the search strategy “Geriatric Assessment” AND “Primary Health Care”, and “Geriatric Assessment” AND “Primary Health Care”. An initial finding of 8,146 articles was obtained. After applying the filters and eligibility criteria, five articles were included for the final analysis, considering the physical and psychological aspects of the elderly person. It was observed that sociodemographic factors directly influence the dependence of the elderly. Depressive symptoms, number of comorbidities, physical activity, self-assessment of their health and family support influence frailty and dependence, triggering low physical and psychological functionality in the elderly, compromising their autonomy to perform daily functions. It was concluded that the functionality of the elderly is directly influenced by extrinsic factors, requiring a redirection of professional practices for the realization of comprehensive health care.